2022
DOI: 10.1364/oe.462869
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation force analysis of nanoparticles with ultra-high numerical aperture metalens

Abstract: Metalens optical tweezers technology has several advantages for manipulating micro-nano particles and high integration. Here, we used particle swarm optimization (PSO) to design a novel metalens tweezer, which can get 3-dimensional trapping of particles. The numerical aperture (NA) of the metalens can reach 0.97 and the average focusing efficiency is 44%. Subsequently, we analyzed the optical force characteristics of SiO2 particles with a radius of 350 nm at the focal point of the achromatic metalens. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…When designing a high NA metalens, the p conforms to the Formula (8), which can prevent spherical aberration to improve the resolution of the imaging. [124][125][126][127][128][129][130][131][132][133] As an illustration, Khorasan et al created titanium dioxide meta-atoms on a silicon dioxide substrate in 2016, a meta-atom with a p of 430 nm was utilized to create a metalens with NA of 0.8 when 𝜆 d was 660 nm, and a nanotarget can be easily identified by the smallest distance between neighboring holes as illustrated in Figure 9 (a). [20] Then, in 2017, Chen et al developed a meta-atom with a p of 150 nm at 𝜆 d of 405 nm, as shown in Figure 9 (b), the oil-soaked metalens had a NA of 1.35, and the Harvard logo can be scanned clearly by the metalens-equipped microscope.…”
Section: Improvements Of Resolutionmentioning
confidence: 99%
“…When designing a high NA metalens, the p conforms to the Formula (8), which can prevent spherical aberration to improve the resolution of the imaging. [124][125][126][127][128][129][130][131][132][133] As an illustration, Khorasan et al created titanium dioxide meta-atoms on a silicon dioxide substrate in 2016, a meta-atom with a p of 430 nm was utilized to create a metalens with NA of 0.8 when 𝜆 d was 660 nm, and a nanotarget can be easily identified by the smallest distance between neighboring holes as illustrated in Figure 9 (a). [20] Then, in 2017, Chen et al developed a meta-atom with a p of 150 nm at 𝜆 d of 405 nm, as shown in Figure 9 (b), the oil-soaked metalens had a NA of 1.35, and the Harvard logo can be scanned clearly by the metalens-equipped microscope.…”
Section: Improvements Of Resolutionmentioning
confidence: 99%
“…Metasurfaces can be used to develop various optical devices, including metalens, 7 , 11 13 vortex generators, 14 16 digitally encoded metasurface, 17 , 18 and polarization conversion 19 24 Therefore, the device design based on metasurface is considered as a promising technology to realize practical nanofunctional devices.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main applications based on metalenses are high numerical aperture metalenses, 22 , 23 achromatic metalenses, 24 , 25 and multifocal metalenses 26 . Chromatic aberration is the phenomenon of deviation of the focal point in the same plane when light beams of different wavelengths are incident.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, metasurfaces can regulate the phase, amplitude, and polarization of electromagnetic waves by introducing phase mutations. Many metasurface devices have been developed in the literature, such as metalens [3][4][5][6][7][8][9], holographic metasurfaces [10][11][12][13][14][15][16], vortex beam generators [17][18][19][20][21], absorbers [22][23][24][25][26], etc. The combination of the subwavelength size and facile fabrication of metasurfaces renders them potentially useful for miniaturized applications.…”
Section: Introductionmentioning
confidence: 99%
“…Let the direction away from the metalens be the positive direction. Equation (4) means that as the ring radius increases, the focus moves toward the positive direction; equation (5) indicates that as the ring radius increases, the focus moves toward the negative direction, as depicted in figure 2.…”
mentioning
confidence: 99%